New materials for luminescent scanning near-field microscopy - Chornii, V.; Chukova, O.; Hizhnyi, Yu.; Nedilko, S.G.; Nedilko, S.A.; Terebilenko, K.; Slobodyanik, M.; Aigouy, L.; Billot, L.; Boyko, V.; Virko, S.; Gomenyuk, O. (Functional Materials, 2013)
Results on synthesis and characterization of the luminescent probes for applications in determination of near-field optical characteristics and spatial distribution of local temperature are presented. Two types of materials are studied: Eu³⁺ doped vanadates LaVO₄, and chromium-doped composites (NaAl(MoO₄)₂/Al₂O₃):Cr. It was shown that submicron-sized particles of the mentioned materials can be used for development of the luminescent probes for near-field optical applications.